Рerspective alloy of the Zr-Nb-Cr system for the new generation of nuclear reactors - Firstov, S.A.; Kuznetsova, T.L.; Brodnikovsky, N.P.; Oryshich, I.V.; Krapivko, N.A. (Вопросы атомной науки и техники, 2018)
Research of the Zr-Nb-Cr system alloys, promising for nuclear power engineering, with the aim of using them at
operating temperatures of 500…600 °С for a new generation of nuclear reactors have been carried out. The
possibility of increasing the high temperature strength, heat resistance, and cast-technological properties of the most
promising serial Zr-1Nb alloy due to alloing its with 1 wt.% Cr. The improvement of properties is explained by the
dispersion hardening of the alloy by the high-temperature, strong intermetallide ZrCr₂. The high-temperature
strength of the Zr-1Nb alloy can be increased by 30% in the temperature range 500…600 °С. The heat resistance of
a promising alloy at a temperature of 500 °C exceeds the heat resistance of an industrial alloy Э635 by 30…50% and
is at the level of heat resistance of the Э110 alloy at 20 hours exposure. The parabolic oxidation constants of the
Zr-1Nb-1Cr alloy increase with increasing temperature and holding time, due to the formation of a dense scale of
Cr₂O₃, ZrO₂ oxides, instead of the brittle scale Nb₂O₅, ZrO₂, which is characteristic for existing serial alloys Э110,
E635, E125. Проведено дослідження сплавів системи Zr-Nb-Cr, перспективних для ядерної енергетики з метою
можливості використання їх при робочих температурах 500…600 °С для атомних реакторів нового
покоління. Встановлено можливість підвищення жароміцності, жаростійкості і технологічності найбільш
перспективного серійного сплаву Zr-1Nb за рахунок легування його 1 мас.% Cr. Поліпшення властивостей
пояснюється дисперсним зміцненням сплаву високотемпературним, міцним інтерметалідом ZrCr₂. При
цьому жароміцність сплаву Zr-1Nb може бути підвищена на 30% в температурному інтервалі 500…600 °С.
Жаростійкість перспективного сплаву при температурі 500 °С перевищує жаростійкість промислового
сплаву Э635 на 30…50% і знаходиться на рівні жаростійкості сплаву Э110 при витримці 20 годин.
Константи параболічного окиснення сплаву Zr-1Nb-1Cr з підвищенням температури і часу витримки
зменшуються в результаті утворення щільної окалини із оксидів Cr₂O₃, ZrO₂ замість крихкої окалини Nb₂O₅, ZrO₂, характерної для існуючих серійних сплавів Э110, Э635, Э125. Проведены исследования сплавов системы Zr-Nb-Cr, перспективных для ядерной энергетики, с целью
возможности использования их при рабочих температурах 500…600 °С для атомных реакторов нового
поколения. Установлена возможность повышения жаропрочности, жаростойкости и технологичности
наиболее перспективного серийного сплава Zr-1Nb за счет легировании его 1 мас.% Cr. Улучшение свойств
объясняется дисперсным упрочнением сплава высокотемпературным, прочным интерметаллидом ZrCr₂.
При этом жаропрочность сплава Zr-1Nb может быть повышена на 30% в температурном интервале
500…600 °С. Жаростойкость перспективного сплава при температуре 500 °С превышает жаростойкость
промышленного сплава Э635 на 30…50% и находится на уровне жаростойкости сплава Э110 при выдержке
20 ч. Константы параболического окисления сплава Zr-1Nb-1Cr с повышением температуры и времени
выдержки уменьшаются в результате образования плотной окалины из оксидов Cr₂O₃, ZrO₂ вместо хрупкой
окалины Nb₂O₅, ZrO₂, характерной для существующих серийных сплавов Э110, Э635, Э125.